THE IMPORTANCE AND FEATURES OF THE PARTICIPATION OF A NOTARY IN CIVIL PROCEEDINGS IN CASES RELATED TO THE APPLICATION OF THE RULES OF INHERITANCE LAW - Karimova Madina Mirzajonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the role, functions, and procedural significance of notaries in civil proceedings related to inheritance law in Uzbekistan. The civil notary system plays a vital part in ensuring the legality, authenticity, and enforceability of inheritance-related actions, including the issuance of certificates of inheritance rights, validation of wills, and property transfers. Through a doctrinal and comparative legal analysis, the paper explores both the legislative framework and practical implementation challenges faced by notaries. The study concludes that while Uzbekistan has a well-structured notarial system on paper, inconsistencies in practice, limited digital integration, and public legal illiteracy hinder its optimal functioning. Strategic reforms are proposed to increase efficiency, legal transparency, and trust in notarial processes in inheritance cases.